Defending Islam Nusantara at the Frontline: Experiment to shape moderatism among Non-structural Nahdliyyin Community - Hamdani, Hamdani (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2021)
Since the promulgation of Islam Nusantara in the 33rd congress of Nahdlatul Ulama, Islamic moderatism has been glorified by its advocates as the religious movement in dealing with social and political changes. This moderate ethos has been inculcated to most Indonesian Muslim by many elites, particularly to nahdliyyin (NU people), to distinguish with the radical and conservative trend of religiosity. This study examines the understanding of wasatiyyah among the youth of nahdliyyin which is organized in a new group called the ‘Pejuang Islam Nusantara’ (PIN, Defenders of Islam Nusantara). Triggered by the criticism and black campaign on Islam Nusantara, this community has a cultural mission to explain and respond the complexity of Islam Nusantara to public both online and offline. This study attempts to capture the worldview of religiosity and political standing point of young generation of nahdliyyin confronting with radical Muslim and Islamist groups by the 2019 presidential election. While the campaign for Islam Nusantara as part of moderatism project of Central Board of Nahdlatul Ulama (PBNU) has been challenged by its opponents, the non-structural agents of nahdliyyin takes initiative to strengthen the campaign by cultural events and educative programs. This study focuses on the youth movement in applying and campaigning Islam Nusantara at grass-root level of the changing Indonesian Muslim constellation.